2022
DOI: 10.1002/prep.202200201
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Testing for Lowest Eutectic Mixture of TNBA/DNTF

Abstract: In this work, electrostatic spraying was used to prepare TNBA/DNTF eutectic mixtures with different mass ratios. The T−X phase diagram and the H−X phase diagram were drawn from the DSC curves of the eutectic mixtures. The morphology, composition, structure, thermal decomposition properties, mechanical sensitivity, thermal sensitivity, and detonation properties of the lowest eutectic were characterized by scanning electron microscope (SEM), energy dispersive X‐ray spectroscopy (EDS), X‐ray diffraction (XRD), Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The low melting points and good thermal stabilities of 2 and 3 make them potential candidates for practical applications, for example, 2 could serve as a potential melt-castable eutectic compound. 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low melting points and good thermal stabilities of 2 and 3 make them potential candidates for practical applications, for example, 2 could serve as a potential melt-castable eutectic compound. 27…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 2 exhibits better detonation and sensitivity properties than previously reported halogen-containing materials like 1,3,5-triiodo-2,4,6-trinitrobenzene (TITNB). 9,27 Moreover, BAM testing methods were carried out to evaluate the safety of compounds 2 and 3 , and they showed that compounds 2 and 3 exhibited ideal safety, being insensitive to impact (IS > 60 J) and friction (FS > 360 J).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl nitroguanidine (MeNQ) [9][10][11][12][13][14], 3,4-dinitrofurazanfuroxan (DNTF) [15][16][17][18], and 1,3,3-trinitroazetidine (TNAZ) [19][20][21][22] based energetic eutectics have been reported over the past 30 years. TNAZ-DNTF eutectic has high thermal stability and energy level but due to the high sensitivity of DNTF its friction sensitivity and impact sensitivity are slightly higher than TNT and B explosives [16].…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al [26] proposed a method of encapsulating DNTF explosive crystals with energetic binder GAP based on the water suspension method to improve their mechanical sensitivity and analyze the desensitization mechanism. In addition to coating modification with binders, DNTF and other explosives, such as DNAN, MTNP, DFTNAN, and TNBA, were optimized for mechanical sensitivity, thermal performance improvement, and energy output characteristics through the low eutectic method, respectively [27][28][29][30]. Previous research on the NC coating of other substances or explosive particles has achieved good desensitization effects, but different coating processes, experimental costs, and ease of operation have also increased many uncertainties.…”
Section: Introductionmentioning
confidence: 99%